Penang Chinese Commerce in the 19th Century : The Rise and Fall of the Big Five - Wong, Yee Tuan (Book collections on Project MUSE., 2015)
The story of Penang would be incomplete without the Big Five Hokkien families (the Khoo, the Cheah, the Yeoh, the Lim, and the Tan). It was the Big Five who played a preponderant role not only in transforming Penang into a regional entrepot and a business and financial base, but also in reconfiguring maritime trading patterns and the business orientation of the region in the nineteenth century. Departing from the colonial vantage point, this book examines a web of transnational, hybrid and fluid networks of the Big Five comprising of family relationship, sworn brotherhood, political alliance a.